2021
DOI: 10.31234/osf.io/ztsda
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Let’s go beyond “the effect of”: Reappraising the impact of ordinary activities on cognition

Abstract: The demands of today’s society for interventions that optimize cognitive abilities and prevent their decline have motivated the translation of scientific findings into applied programs. Ordinary activities such as physical exercise and playing a musical instrument have witnessed the growth of evidence emphasizing their benefits on cognition and the brain. Here we propose several issues that need consideration before speculating on the implications of a positive result of an individual study and implementing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The exercise–cognition topic is not immune to this. Transparent practices throughout the research process (e.g., reporting bias-corrected effects) and accurate dissemination of scientific findings through the media would definitely improve the situation 41 . Nevertheless, this is a necessary but not sufficient step.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise–cognition topic is not immune to this. Transparent practices throughout the research process (e.g., reporting bias-corrected effects) and accurate dissemination of scientific findings through the media would definitely improve the situation 41 . Nevertheless, this is a necessary but not sufficient step.…”
Section: Discussionmentioning
confidence: 99%
“…Greater benefits were observed in younger participants. This suggests that physical activity may have a stronger and more lasting effect on general cognitive skills during a sensitive period [59]. In addition, previous meta-analyses have found that physical activity has a positive impact on executive function and academic performance in prepubescent children [60].…”
Section: Age As a Moderatormentioning
confidence: 91%